2012
DOI: 10.1038/pr.2012.154
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of two inodilators in neonates undergoing cardiovascular surgery

Abstract: Background: Inodilators are routinely used in cardiovascular surgery with cardiopulmonary bypass (cPB). Information regarding safety and tolerability of the novel molecule, levosimendan (LeVO), in newborns is anecdotal; no pharmacokinetic data in this population are available. Methods: This was a phase I, randomized, and blinded study. Neonates undergoing surgical repair for congenital heart defects received stepwise dose increases of milrinone (MR; 0.5-1 μg/kg/min, n = 9) or LeVO (0.1-0.2 μg/kg/min, n = 11) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 35 publications
0
65
0
1
Order By: Relevance
“…However, the peripheral oxygenation differed between both groups along this time period, showing an increase in the levosimendan group and a decrease in the milrinone group. In the same study, there were no significant differences between groups regarding serial echocardiography parameters; however lactate level was increased in the milrinone group [63].…”
Section: Evidence and Pd Effectsmentioning
confidence: 69%
See 1 more Smart Citation
“…However, the peripheral oxygenation differed between both groups along this time period, showing an increase in the levosimendan group and a decrease in the milrinone group. In the same study, there were no significant differences between groups regarding serial echocardiography parameters; however lactate level was increased in the milrinone group [63].…”
Section: Evidence and Pd Effectsmentioning
confidence: 69%
“…Cerebral and peripheral tissue oxygenation measured by NIRS have been found to be increased with levosimendan in a group of newborns undergoing corrective surgery for heart disease [63].…”
Section: Evidence and Pd Effectsmentioning
confidence: 99%
“…Twenty-one studies were identified to use peripheral muscle NIRS measurements as a single method [1,3,6,7,8,9,10,11,12,13,14,15,16,17,18,19,23,24,25,27,28] (table 1), 17 studies combined cerebral and peripheral muscle NIRS measurements [20,21,22,29,30,31,32,33,34,35,36,37,38,39,40,41,42] (table 2) and 1 study used multi-site NIRS measurements [43] (table 2) in human neonates. Two randomized studies were identified [12,36]. Two additional publications were included because they provided important general information about peripheral NIRS measurements [44,45].…”
Section: Resultsmentioning
confidence: 99%
“…In a phase I, randomized study, Pellicer et al [36] investigated the haemodynamic effects of the routinely used milrinone, a selective phosphodiesterase III inhibitor, that has inotropic and lusitropic effects on the myocardium and a relaxing effect on the vascular muscle, and the novel molecule levosimendan in neonates undergoing cardiovascular surgery using NIRS measurements to assess changes in cerebral and peripheral perfusion and oxygenation. The study provided data on the early intraoperative use of both inodilators, but also emphasized the persistent haemodynamic effects of levosimendan after the end of drug infusion.…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, milrinone was recently tested in the context of postsurgical support for neonates after cardiovascular surgery. 17 Milrinone now seems like a pediatric treatment option that would greatly benefit from pharmacokinetic characterization and dose optimization. For doing so, a low plasma volume analytical method and a higher degree of sensitivity are required in particular for inhaled milrinone studies.…”
Section: Introductionmentioning
confidence: 99%